VERBAL COMPLEMENTS IN ENGLISH AS FOUND IN THE JAKARTA POST - Bonar Gurning; Suryaningsih Situngkir (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study deals with Verbal Complements as Found in The Jakarta Post issued in September 23, 2010. The objective of the study is to find out the functions of verbal complements in the sentences found in The Jakarta Post. Speaking of verbal complements, the writers use the theory of Aarts and Aarts to analyze the data. Aarts and Aarts distinguish the verbal complements into six types: direct object (DO),indirect object (IO), benefactive object (BO), subject attribute (SA), object attribute(OA), and predicator complement (PC). In accomplishing this study, the writers took the data from The Jakarta Post and choose the sentences that contain verbal complements. So, the total number are 225 data. Verbal complements which function as direct object are 92 data, verbal complements which function as indirect object are 12 data, verbal complements which function as benefactive object are 15 data, verbal complements which function as subject attribute are 72 data, verbal complements which function as object attribute are 25 data and verbal complements which function as predicator complement are 9 data. The result of analysis shows that the sentences in The Jakarta Post using verbal complements functioning as direct object (DO) is the highest rank, and followed by subject attribute (SA), object attribute (OA), benefactive object (BO), indirect object (IO) and predicator complement (PC). Predicator complement form of prepositional phrase, finite clause and non finite clause are not found in the data.